Dosimetric Impact of Interfractional Variations in Prostate Cancer Radiotherapy—Implications for Imaging Frequency and Treatment Adaptation - Bostel, Tilman; Sachpazidis, Ilias; Splinter, Mona; Bougatf, Nina; Fechter, Tobias; Zamboglou, Constantinos; Jäkel, Oliver; Huber, Peter E.; Baltas, Dimos; Debus, Jürgen; Nicolay, Nils H. (Frontiers in Oncology, 2019)
Background and purpose To analyze deviations of the applied from the planned doses for definitive prostate cancer radiotherapy depending on anatomic variations and imaging frequency. Materials and methods Daily in-room CT imaging was performed in treatment position for 10 patients with prostate cancer undergoing radiotherapy (340 fraction CTs). Applied fraction doses were recalculated on daily images, and voxel-wise dose accumulation was performed using a deformable registration algorithm. For weekly imaging, weekly position correction vectors were derived and used to rigidly register daily scans of that week to the planning CT scan prior to dose accumulation. Applied and prescribed doses were compared, and derived TCP and NTCP values were calculated. Results Daily CT-based repositioning resulted in non-significant deviations of all analyzed dose-volume, conformity and uniformity parameters to the CTV, bladder and rectum irrespective of anatomic changes. Derived average TCP values were comparable, and NTCP values for the applied doses to the bladder and rectum did not significantly deviate from the planned values. For weekly imaging, the applied D2 to the CTV, rectum and bladder significantly varied from the planned doses, and the CTV conformity index and D98 decreased. While TCP values were comparable, the NTCP for the bladder erroneously appeared reduced for weekly repositioning. Conclusions Daily, but not weekly imaging resulted in only negligible deviations of the applied from the planned doses for prostate radiotherapy. Weekly imaging may not be adequately reliable for adaptive treatment delivery techniques for prostate. This work will contribute to devising adaptive re-planning strategies for prostate radiotherapy.